التفسير العلمي لأحاديث التمر في ضوء جمع روايات الحديث والاكتشافات العلمية الجديدة - Ismail, Y. (Universiti Sains Islam Malaysia, 2024)
The Hadiths of the Prophet regarding benefits of dates or scientifically known as Phoenix dactilyfera has gain so much attention from the scientist of Islamic knowledge and the modern sciences. Most researches presented in the topic focus on the benefit of dates in dealing with poisoning as it were clearly stated in the Hadith, furthermore some new scientific findings prove that the benefits of dates are far beyond that. Besides, the benefits of dates in dealing with black magic is still undiscovered by the modern sciences, even though some people claim to explain it scientifically, it is no more than an example of pseudoscience. It is also important to mention that most of the books published in the field of al-‘Ijaz al-‘ilmi related to the dates issue, especially those written in Arabic language has been observed to repeat the same scientific information regarding the benefits of dates despite the presence of new scientific researches and findings. On the other hand, some researches in this subject also has been notably neglect the importance of collecting all related texts of the Hadith before starting to interpret it, which is a vital step in understanding the Hadith. Therefore this research aims at understanding the Hadith regarding the benefits of dates through collecting all related Hadith in the topic and further interpreting it scientifically by referring to new scientific researches available.